Travis Hirschi’s Social Control Theory Perspective on the Relevance of Early Marriage and Sexual Violence - Busthomi Arifin; Rusmilawati Windari; Tolib Effendi (Universitas Negeri Semarang, 2024)
Crime as an inherent problem throughout the history of the human journey continues to trigger a never-ending discussion, including in the context of early marriage and sexual violence. The purpose of writing this article is to explore the relevance between sexual violence and early marriage in the view of criminology, especially from the perspective of social control theory initiated by Travis Hirschi, so that later efforts can be found to prevent the practice of early marriage from taking root. The research method applied is normative juridical research with literature study techniques. The results showed that the relevance between early marriage and sexual violence is closely related. Early marriage and sexual violence can be said to be a domino effect. Another relevance lies in the means of control, if sexual violence is overcome (controlled) then early marriage also does not occur (controlled), and vice versa. According to Travis Hirschi's social control theory, there is a causal chain of the relevance of early marriage to sexual violence which includes individual attachment to parents and school (attachment), commitment not to disappoint the important things in one's life (commitment), individual involvement in a positive activity (involvement), and belief in good noble values in the context of early marriage and sexual violence (belief).